LncRNA SNHG15 regulates EGFR-TKI acquired resistance in lung adenocarcinoma through sponging miR-451 to upregulate MDR-1 - Huang, Jiayuan (Cell Death Dis, 2020)
Lung adenocarcinoma (LUAD) is the main component of non-small-cell lung cancer (NSCLC) and causes a great health concern globally. The top priority of LUAD treatment is to deal with gefitinib resistance. Long non-coding RNAs are certified to modify gefitinib resistance in the course of tumor aggravation. The study focuses on addressing the function of small nucleolar RNA host gene 15 (SNHG15) on modifying gefitinib resistance in LUAD. Previously, NOTCH pathway is implicated in LUAD chemo-resistance. SNHG15 level was boosted following the depletion of NOTCH-1 in A549/GR and H1975/GR cells. Functional studies indicated that SNHG15 and multidrug resistance protein 1 (MDR-1) were overexpressed and possess tumor-promoting functions in gefitinib-resistant LUAD cells while miR-451 was downregulated and possess tumor-suppressive behaviors in gefitinib-resistant LUAD cells. Mechanically, the SNHG15 was cytoplasmically distributed in GR LUAD cells. In addition, SNHG15 released MDR-1 from the suppression of miR-451, leading to MDR-1 promotion. In addition, the elevation of SNHG15 could be attributed to ZEB1. Rescue assays highlighted that downstream molecules MDR-1 and miR-451 could reverse the effects of SNHG15 downregulation on gefitinib-resistant LUAD cells. SNHG15 could alter chemo-resistance of LUAD cells to Gefitinib via regulating miR-451/MDR-1, which could be inspiring findings for the advancement of chemo-therapies for LUAD.